Experimental identification of the force and moment characteristic of symmetrically and non-symmetrically profiled annular seals - Kuhr, Maximilian M. G.; Pelz, Peter F. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
In modern turbomachinery, the performance and reliability is often limited by shaft vibrations induced by fluid film forces and moments of (i) plain or (ii) profiled annular seals. Therefore, these narrow annuli are mainly responsible for the overall system behaviour, i.e. safe operation and maintenance intervals. However, many studies focus only on the characteristics from the forces due to the translational motion, although the influence of the rotordynamic tilt and moment coefficients is well known. Therefore, these additional coefficients are much less researched. Especially, for profiled seals, the availability of reliable experimental data for validation purpose is rare. To overcome this fact, a test rig is operated at the Chair of Fluid Systems at the Technische Universität Darmstadt. The generic experiments presented here investigate the force and moment characteristic of plain, symmetrically profiled and non-symmetrically profiled annular seals within the relevant parameter range for turbulent flows in pumps. The investigations focus on the influence of the annulus length as well as the pressure difference across the annulus.